The Megilla of Esther and the Magnificat of Mary of Nazareth - Di Luccio, Pino (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
The figure of Mary of Nazareth, as portrayed in her Magníficat, is closely related to Esther, the main character of the Megillah which bears her name. In both narratives there is a major theme: the reversal of fortune, joined to the matter of «universalism» described as communion between generations, as extension of relationships, and as a sharing in a common history, characterized by the experience of Lord’s mercy.
Keywords: woman; Bible; Mary; Esther; Magnificat; reversal of fortune; universalism